Evidence for proto-Philippine nominative marking - Reid, Lawrence A. (Philippine Journal of Linguistics, 1979)
In a paper published in the proceedings of the Second International Conference on Austronesian Linguistics (Reid 1978), I proposed tentative reconstructions of a number of grammatical morphemes for Proto-Philippines. Since presenting that paper, an insightful but to date unpublished paper by Bill Seiter (University of California at San Diego), ?Information questions in the Philippine languages?, has come to my attention. In this paper, Seiter attempts to reconstruct aspects of the syntax of Information Questions in Proto-Philippines on the basis of evidence from seven of the eight ?major? languages of the Philippines: Tagalog, Bikol, Cebuano, Hiligaynon, Ilokano, Pangasinan, and Kapampangan. Seiter proposes a number of reconstructed forms for Proto-Philippines, some of which (such as Genitive *na and *ni and Nominative *si) agree with the reconstructions I have proposed. However, one of the reconstructions which he proposes and which figures fairly prominently in the discussion in his paper is, I believe, an unwarranted reconstruction. The form in question is Seiter?s proposed *a ?common Nominative determiner? (This gloss matches my usage. Seiter?s gloss would be ?non-human Topic marker?). Since this reconstruction has been proposed elsewhere (Foley 1976), it is probably worthwhile to critically reexamine all of the evidence for the Nominative reconstructions, and to decide whether it has been interpreted correctly. In the first section the evidence given by Seiter for the reconstruction of *a will be examined. In the second section, the evidence for the reconstruction of *ʔi will be examined. In the final section, evidence for the reconstruction of other possible Nominative markers in Proto-Philippines will be examined.